2014
DOI: 10.1016/j.coph.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Role for β-arrestin in mediating paradoxical β2AR and PAR2 signaling in asthma

Abstract: G protein-coupled receptors (GPCRs) utilize (at least) two signal transduction pathways to elicit cellular responses including the classic G protein-dependent, and the more recently discovered β-arrestin-dependent, signaling pathways. In human and murine models of asthma, agonist-activation of β2-adrenergic receptor (β2AR) or Protease-activated-receptor-2 (PAR2) results in relief from bronchospasm via airway smooth muscle relaxation. However, chronic activation of these receptors, leads to pro-inflammatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 55 publications
(82 reference statements)
1
37
0
Order By: Relevance
“…Cumulative reports indicate that PAR2 activation is associated with the pathogenesis of allergic airway inflammation . PAR2‐deficient mice could not be induced airway allergy .…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative reports indicate that PAR2 activation is associated with the pathogenesis of allergic airway inflammation . PAR2‐deficient mice could not be induced airway allergy .…”
Section: Discussionmentioning
confidence: 99%
“…β2AR activation enhances adenylate cyclase activity and cAMP synthesis, which promote smooth muscle relaxation in airways and blood vessels, enhance ciliary beating, enhancing mucin clearance. 35,36 However, repeated β2AR stimulation leads to receptor desensitization through phosphorylation of GRK2, which promotes phosphorylation and internalization of the β2AR. 12,37 This receptor activation/desensitization is complex with different mechanisms involved in different settings, although phosphorylation of β2AR is central to all.…”
Section: Discussionmentioning
confidence: 99%
“…40). In vivo studies have reported that barrestin-2 null mice have shown an attenuated asthma phenotype, and we have recently shown that administration of b 2 AR ligands capable of activating ERK1/2 in vitro (10, 12) restore the asthma-like phenotype in PNMT-KO mice, and do not attenuate the asthma-like phenotype in WT mice (16).…”
Section: Discussionmentioning
confidence: 99%